A circular approach for landfill leachate treatment: Chemical precipitation with biomass ash followed by bioremediation through microalgae. Issue 3 (June 2021) - Viegas, Catarina; Nobre, Catarina; Mota, André; Vilarinho, Cândida; Gouveia, Luísa; Gonçalves, Margarida
Abstract: The aim of this work was to study an integrated approach for landfill leachate remediation comprising chemical precipitation with biomass bottom ash as a pre-treatment to reduce color and turbidity followed by bioremediation through microalgae treatment for effluent disposal. Optimal pre-treatment conditions were determined through batch experiments and were found to be 160 g L −1 ash dose, 96 h of contact time, overhead agitation at 15 rpm and ash particle size below 500 µm. These conditions led to removal efficiencies of 74.3% for chemical oxygen demand and 98.5% for color. Large quantities of sludge containing excess biomass ash and precipitated compounds were formed during the pre-treatment. To minimize solid disposal, this sludge was tested as a raw material for cementitious and aggregate substitute in mortar formulations. Following the pre-treatment, the leachate was inoculated with six different microalgae species to evaluate their ability to grow in such a recalcitrant effluent and remediate it. After a period of 27 days biomass concentration from 0.4 to 1.2 g L −1 were achieved for the tested microalgae. Removal efficiencies were in the range of 18–62% for COD, 63–71% for N, and 15–100% for P. At the end of the treatment, algal biomass was characterized regarding protein, lipid, fatty acids, carbohydrate, and ash contents. This approach allows a low-cost remediation of these recalcitrant effluents when compared with the present options that include inverse osmosis, and the valorization of ash-rich precipitates and microalgae biomass improves the sustainability of the overall process. Graphical Abstract: ga1 Highlights: Precipitation with biomass ash is a promising pre-treatment for landfill leachate. Pre-treatment reduced 74% of COD and 99% of color. Microalgae were able to remediate undiluted pretreated landfill leachate. Bioremediation showed reductions of 62%, 71% and 100% for COD, N and P, respectively. Pre-treatment by-products showed potential to be used in mortar formulations.